Survey of synthetic respondents: new opportunities or threats to data reliability? - Kuchko, Elena E.; Vishnyakova, Margarita V.; Marchuk, Yana I. (Journal of the Belarusian State University. Sociology, 2026)
The article explores the main applications of artificial intelligence models in the professional work of sociologists. Particular attention is paid to the use of large language models and their role in generating responses from synthetic respondents. It is noted that the use of synthetic respondents allows for faster research, access to hard-to-reach groups, and the elimination of the interviewer effect. At the same time, methodological limitations are emphasised, including the inability to account for emotional reactions, the reduction of social context, and the low quality of training of large language models caused by the unavailability of training datasets.